Identification of promising sources of hulless barley (Hordeum vulgare L.) for important quality traits - Kumar, Dinesh; Verma, Ramesh Pal Singh; Narwal, Sneh; Singh, Jogendra; Malik, Rekha; Kharub, Ajit Singh; Singh, Gyanendra Pratap (Journal of Cereal Research, 2021)
Barley is one of the unique cereals having health promoting properties in its grains. There is a renewed interest in food barley in past few years and need is being felt for high yielding hulless genotypes with superior food quality parameters. In this study 19 land races collected from Leh and Ladakh region, four exotic germplasm introductions, breeding lines and six released hulless cultivars were evaluated in 2017-18 for seven grain quality parameters. Promising genotypes for grain beta glucan content and thousand kernel weight have been identified. A positive correlation has been observed between grain beta glucan content and protein content.